Implementation of Android Platform Application "PSG Balita" ISO/IEC 25010 Standardized to Improve Nutritional Status Data for Toddler - Agus Hendra Al Rahmad; Ichsan Ichsan; Ratna Wilis (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The need to obtain data and information on nutritional status based on the name by address is required for nutrition reporting. Thus, we should use technological advances to support the quality of toddler nutritional status data. The "PSG Balita" application has ISO/IEC 25010 standards and allows proper recording. This study aimed to measure the effect of implementing an Android-based "PSG Balita" application with ISO/IEC 25010 standards on the quality of toddler nutritional status data. A quasi-experimental research design was conducted in Banda Aceh City in 2021, involving 30 nutritionists at a health center. Data were collected through interviews and observations using a questionnaire that included timeliness, completeness, accuracy, and usefulness. The intervention was conducted through training using the Android-based "PSG Balita" application for one month. Data analysis using the Repeated Measures ANOVA test. Results, the "PSG Balita" application has shown a significant effect in improving the quality of nutritional status data for children under five (p < 0.05). It was found that after implementing the application for one month, the aspects of timeliness (p= 0.000), completeness (p= 0.000), accuracy (p= 0.001), and usefulness (p= 0.002) could improve the quality of nutritional status data for toddlers. In conclusion, the "PSG Balita" application has made it easier for users to monitor the nutritional status of a toddler, has good accuracy, and allows early identification of the risk of malnutrition. The "PSG Balita" application, which adheres to ISO/IEC 25010 standards, can enhance the accuracy of nutritional status data for young children.